AKSELERASI DIGITALISASI TATA KELOLA KEUANGAN DAN PERSEDIAAN, FORMALISASI LEGALITAS, DAN STRATEGI PENGEMBANGAN AKSES PASAR PADA UMKM WAROENG MAMA FIRMAN DI KABUPATEN BOGOR - Sulaeman, Iman (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze and implement strategic assistance for Waroeng Mama Firman MSME in Bantarjati, Bogor Regency. The main focus includes financial management transformation, business legality compliance, and market access development. The primary issues identified are manual recording systems, the absence of a business identity (NIB), and limited distribution reach. The research method is qualitative with an Action Research approach. Data were analyzed using SWOT and TOWS matrices to formulate strategic solutions. The results show that the implementation of the BukuWarung digital bookkeeping application significantly increased the accuracy of financial reports. Facilitation through the Online Single Submission (OSS) system successfully issued NIB as the formal basis for the business. In the aspect of market access development, optimizing distribution channels through social media and delivery services has proven to expand the customer reach beyond the conventional radius. The synergy between operational digitalization and market access expansion is a key factor in strengthening MSME competitiveness against modern retail.